Dampak dan Strategi UMKM (Usaha Mikro Kecil Dan Menengah) Menghadapi The “New Normal” - Endah Marendah Ratnaningtyas (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2020)
Micro, Small and Medium Enterprises (MSMEs) are business activities capable of expanding employment opportunities, providing broad economic services to the community, playing a role in the process of equalization and increasing community income, encouraging economic growth, and playing a role in realizing national stability. The purpose of this study is to determine how MSMEs increase competitiveness in facing the